eOS: The exercise operating system - Mendes, Rui (2018)
We present an architecture for a system for creating, adapting and evaluating programming exercises for students. The system is capable of generating exercise skeletons, automatically creating inputs and outputs, provide a way of creating a large number of exercises programmatically and allowing students to solve them while giving them feedback. Furthermore, it allows the creation of special comparators that can check whether the output of a given submission is equivalent to the expected one or simply check whether the above mentioned output corresponds to a correct solution.